Utilization of a highly adaptable murine air pouch model for minimally invasive testing of the inflammatory potential of biomaterials - Woitschach, Franziska; Kloss, Marlen; Kischkel, Sabine; Macháček, Tomáš; Reinholdt, Cindy; Senz, Volkmar; Schlodder, Karsten; Löbermann, Micha; Grabow, Niels; Reisinger, Emil C.; Sombetzki, Martina (Frontiers in Bioengineering and Biotechnology, 2024)
The biocompatibility of an implanted material strongly determines the subsequent host immune response. After insertion into the body, each medical device causes tissue reactions. How intense and long-lasting these are is defined by the material properties. The so-called foreign body reaction is a reaction leading to the inflammation and wound healing process after implantation. The constantly expanding field of implant technology and the growing areas of application make optimization and adaptation of the materials used inevitable. In this study, modified liquid silicone rubber (LSR) and two of the most commonly used thermoplastic polyurethanes (TPU) were compared in terms of induced inflammatory response in the body.We evaluated the production of inflammatory cytokines, infiltration of inflammatory cells and encapsulation of foreign bodies in a subcutaneous air-pouch model in mice. In this model, the material is applied minimally invasively via a cannula and in one piece, which allows material testing without destroying or crushing the material and thus studying an intact implant surface.The study design includes short-term (6 h) and long-term (10 d) analysis of the host response to the implanted materials. Air-pouch-infiltrating cells were determined by flow cytometry after 6 h and 10 d. Inflammation, fibrosis and angiogenesis markers were analyzed in the capsular tissue by qPCR after 10 d. The foreign body reaction was investigated by macroscopic evaluation and scanning electron microscopy (SEM). Increased leukocyte infiltration was observed in the air pouch after 6 h, but it markedly diminished after 10 d. After 10 d, capsule formations were observed around the materials without visible inflammatory cells. For biocompatibility testing materials are often implanted in muscle tissue. These test methods are not sufficiently conclusive, especially for materials that are intended to come into contact with blood. Our study primarily shows that the presented model is a highly adaptable and minimally invasive test system for candidate materials to test their inflammatory potential and foreign body reaction and offers more precise analysis options by means of flow cytometry.